Teacher Performance Based on Organizational Citizenship Behavior and Individual Characteristics - Sherly Sherly; Edy Dharma (Trigin Publisher, 2023)
The aim of this research is to investigate how organizational citizenship behavior and individual characteristics impact the performance of teachers at Sultan Agung Pematang Siantar Private High School both simultaneously and partially. This research employs a combination of literature review methodology and field research. The population in this study is the total number of permanent teachers at Sultan Agung Pematang Siantar Private High School which amounts to 38 people. This study incorporates both qualitative and quantitative data. Both primary and secondary data sources were utilized in this study. Data gathering involved the use of questionnaires, interviews, and documentation, with research instruments being subjected to validity and reliability tests. The data analysis techniques used are quantitative descriptive analysis, namely normality tests, regression, hypothesis testing and correlation and determination tests. The findings from this research can be summarized (1) organizational citizenship behavior and individual characteristics have a substantial and positive impact on teacher performance both simultaneously and partially; (2) There is moderately high correlation between organizational citizenship behavior and individual characteristics to teacher performance